Communication and visitor factors contributing towards heritage visitors' mindfulness. Issue 1 (2nd January 2020) - Tan, Poh Ling; Md Noor, Shuhaida; Rasoolimanesh, S. Mostafa; Mustafa, Hasrina
ABSTRACT: This study aims to examine the effect of communication factors (e.g. uses of questions and multisensory media) and visitor factors (e.g. high level of interest and visualisation) on visitors' mindfulness. Mindfulness refers to a state of mind in which an individual is actively processing information from their environment. Past literature has suggested that being mindful helps increase visitor understanding, learning and satisfaction. While a number of studies have explored the effects of communication factors on mindfulness, little is understood about the effects of visitor factors. Moreover, most previous studies of mindfulness have employed qualitative research methodologies. The present study relies on a survey of 390 local and international tourists to George Town, Penang (Malaysia) – a UNESCO World Heritage Site. Partial least squares-structural equation modelling (PLS-SEM) has been employed to analyse the data. The results demonstrate the significant effect of both communication factors and visitor factors on mindfulness. The findings of the study suggest that visitor mindfulness might be improved by incorporating questions, multisensory media, level of interest and visualisations in the design of the visitor experience at the heritage sites.